Mortality and the business cycle: evidence from an estimated DSGE model for Germany - Farzaneh Shamsfakhr (International Economics and Economic Policy, 2024)
This study addresses the relationship between transitory macroeconomic conditions and health by analyzing the dynamics of death over business cycle fluctuations in Germany during 1998:Q4–2014:Q4. A dynamic stochastic general equilibrium (DSGE) model with population growth is developed to incorporate demographic shocks including mortality. The estimation results indicate that mortality in Germany is counter-cyclical, suggesting that health in Germany deteriorates during recessions whereas it improves over economic expansions. Moreover, the structure of mortality is found to vary with respect to the business cycles. While for most of the sample period non-working population seems to be more exposed to death during recessionary times, there are evidences of higher fatality of working people in Germany during the recent financial and economic crisis. In the light of the demographic change that Germany is currently experiencing, findings of this study have important implications for health policies concerning aging as well as working-age population.
Keywords: 330